2016
DOI: 10.1002/14651858.cd002218.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics versus no treatment for toxoplasma retinochoroiditis

Abstract: Analysis 1.1. Comparison 1 Antibiotic versus placebo or no treatment, Outcome 1 Mean change in BCVA at 12 months. Analysis 1.2. Comparison 1 Antibiotic versus placebo or no treatment, Outcome 2 Recurrence of lesions.. .. . Analysis 1.3. Comparison 1 Antibiotic versus placebo or no treatment, Outcome 3 Improvement in intraocular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 27 publications
2
50
0
4
Order By: Relevance
“…A 2011 report by the American Academy of Ophthalmology concluded that there is no level I evidence to support the routine use of antimicrobials in acute OT treatment in immunocompetent patients (137). A recent Cochrane review of randomized trials of antimicrobial treatment versus placebo or no treatment also did not find evidence supporting visual acuity improvement with treatment (138). Nonetheless, many uveitis experts treat lesions that are vision threatening or have significant inflammation because of fear of vision loss (136).…”
Section: Ocular Toxoplasmosismentioning
confidence: 99%
“…A 2011 report by the American Academy of Ophthalmology concluded that there is no level I evidence to support the routine use of antimicrobials in acute OT treatment in immunocompetent patients (137). A recent Cochrane review of randomized trials of antimicrobial treatment versus placebo or no treatment also did not find evidence supporting visual acuity improvement with treatment (138). Nonetheless, many uveitis experts treat lesions that are vision threatening or have significant inflammation because of fear of vision loss (136).…”
Section: Ocular Toxoplasmosismentioning
confidence: 99%
“…In immune competent individuals the most widely accepted regimen involves the use of the folic acid antagonist pyrimethamine with or without added sulfadizine with the main application being the treatment of Toxoplasma associated eye disease (Pradhan et al 2016). In addition to having toxicities related to its mechanism of action as noted above, this mechanism is generally ineffective against the bradyzoite form of the organism and thus cannot be used to treat tissue cysts, the form of the organism resident in the central nervous system of immune competent individuals.…”
Section: Current Status Of Anti-toxoplasma Medicationsmentioning
confidence: 99%
“…Sin embargo, existe aun controversia en relación a la combinación de varias drogas, el uso de tratamiento sistémico versus intravítreo y la utilización de esteroides. De acuerdo con la última revisión Cochrane, el tratamiento de la corioretinitis por toxoplasmosis podría disminuir el (3,(16)(17)(18) riesgo de recurrencia . Especial cuidado debe tenerse en pacientes inmunocomprometidos, con l e s i o n e s a c t i va s d e l a c á m a r a p o s t e r i o r , considerando que pueden presentar formas (19) fulminantes de TO .…”
Section: Discussionunclassified